The Application of Financial Reporting Based on SAK-EMKM and the Utilization of Accounting Information Technology on the Financial Report Quality of UD Neo Cirasa Bakery - Hadi, Auzien Ziqri; Syafina , Laylan; Hasibuan, Nur Fadhilah Ahmad (Penerbit Goodwood, 2024)
Purpose: This study aims to analyze the implementation of SAK-EMKM-based financial statements and the utilization of accounting information technology on the quality of UD Neo Cirasa Bakery's financial reports. Research methodology: This research uses a qualitative descriptive method with interviews, observations, and documentation as instruments. Primary data were obtained from UD Neo Cirasa Bakery’s management staff. Results: The results show that the application of SAK-EMKM is in line with the preparation of financial position and income statements, but has not fully been applied to notes to financial statements due to limited accounting personnel. Limitations: This study is limited to a single case study of UD Neo Cirasa Bakery, which may not be representative of all MSMEs in the industry. The research period was confined to one fiscal year, and the findings are specific to the Indonesian MSME context. Additionally, the study relies heavily on qualitative data from interviews, which may be subject to participant bias and interpretation limitations. Contribution: This research is beneficial for MSMEs in understanding the importance of implementing SAK-EMKM and information technology to improve financial reporting quality.